'Extraordinary translations' and 'loathsome commentaries': Quranic translation and the politics of the Tamil language, c. 1880–1950. Issue 3 (3rd July 2019) - Tschacher, Torsten
ABSTRACT: The practice of translating the Quran in Muslim societies is often understood by reference to the Reformation and Protestant Bible translations. The non-translatability of the Quran is counterposed to the radical translatability of the Bible. Furthermore, instances of Quranic translation in Muslim societies are often explained with reference to 'reform movements'. The article's aim is to demonstrate the problems that arise from abstracting the experience of post-Reformation Europe into a general theory of the impact of scriptural translation. For this purpose, I will interrogate the case of Tamil translations of the Quran, where Quran translations from the 1920s onwards eclipsed an older history of Quranic translation in the language.